A biometric-based system for cyber security - Su, Lin Khine (Nanyang Technological University, 2020)
Technological advancements have made the world a better place and the world is becoming ever more reliant on these technologies. This dependence has come at a cost as the technologies that we use to make our lives convenient has also exposed us to the threats of cyberattacks. The rise in such activities has made cybersecurity a necessary component in modern-day digital and communications technology. The goal of the project is to enhance cybersecurity by incorporating face recognition technology with traditional password authentication. This approach is called multi-factor authentication and it is adopted widely in various fields like banking, e-commerce, and social networking. The system for this project is developed using MATLAB MathWorks with the integration of MySQL database and the face recognition technology is implemented using machine learning algorithms like SVM and AlexNet deep learning. Verification of the system's performance is done by conducting set of experiments. The result of these experiments show AlexNet achieved the highest total accuracy of 93%.